Faktor Keuangan dan Return on Asset melalui Debt Equity Ratio - Dirvi Surya Abbas; Arry Eksandy; Mohammad Zulman Hakim (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2020)
The purpose of this study is to determine the effect of the Current Ratio, Debt Turnover Ratio, Inventory Turnover Ratio, Total Asset Turnover Ratio and Debt to Equity Ratio to the Ratio of Return on Assets. The sample used was 12 automotive sub-sector companies and components that met the criteria for the distribution of 2011-2018. The method of collecting data using purposive sampling method. Data is obtained from annual reports that are listed on the Indonesia Stock Exchange. The analytical tool used in this study uses multiple linear regression analysis. The results of this study indicate that the Current Ratio and Total Asset Turnover Ratio have a significant positive effect on the ratio of return on assets. Variable Accounts Receivable Ratio and Debt to Equity Ratios have a significant negative effect on the ratio of return on assets. Based on path analysis and the Sobel Test, it can be concluded that the debt to equity ratio only mediates the effect of the Current Ratio to the Ratio of return on assets.